AKURASI QUICK COUNT DALAM MENYAJIKAN INFORMASI HASIL PEMILIHAN UMUM TAHUN 2024 - Mulyadi, Dedi; Permatasari, Ira; Hanifah, Jihan; Januwati, Pusfa; Azzahra Nurdava, Sativa; Kurnia, Farhan Dwi (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2024)
The Presidential Election and Legislative Election are important processes in determining future leaders. The elections are carried out using a different concept, namely with a new method known as quick count, which involves fast counting with a high level of accuracy, which is the benchmark in determining the winner. in the presidential and legislative election process, this process is closely related to the concept of democracy, according to which power is completely in the hands of the people, problems related to quick counts in voting, namely there are inaccuracies in the election process, and indications of fraud have the potential to have consequences law in accordance with the provisions in force in Indonesia, so that significant changes can occur in the occurrence of popular protests to demand justice and honesty in the election process. This is related to the method used is a qualitative method which aims to test the hypothesis proposed for an integrative analysis and more conceptually to find, identify, process and analyze problems in order to understand the meaning, significance and relevance to control certain variables, to understand the cause-and-effect relationship between variables, Finally, the statistical methods used, whether quick counts, exit polls or surveys should be able to correlate with public aspirations in improving welfare and the public's bargaining power towards power. The role of statistical methods can summarize the desires of the community, to at least be published and become material for joint evaluation for the government, stakeholders, the public, the market and institutions with an interest in it so that they can be more accurate and honest in the context of elections in the future. in accordance with a combination system between the quick count and the previous election system.